2018
DOI: 10.5272/jimab.2018241.1928
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Risk Assessment for Depression in Community Pharmacy- Pilot Study

Abstract: SUMMARYBackground: Depression is the most common mental illness affecting more than 300 million people worldwide and is a significant risk factor for morbidity and mortality. In most cases, it may remain undetected in primary care. Comprehensive screening tools for diagnosing depression might facilitate early detection. As the most accessible health professionals, pharmacists can play an important role in helping to identify individuals at risk.Objective: To differentiate individuals at risk of depression who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…40 Different studies confirmed the capability of the pharmacist to be involved in screening programs and risk assessment services for depression. 41,42 Kondova et al 43 identified that 70% of all patients screened in a community…”
Section: Education Of the Patient And His/her Relatives/ Caregivers Gmentioning
confidence: 99%
“…40 Different studies confirmed the capability of the pharmacist to be involved in screening programs and risk assessment services for depression. 41,42 Kondova et al 43 identified that 70% of all patients screened in a community…”
Section: Education Of the Patient And His/her Relatives/ Caregivers Gmentioning
confidence: 99%
“…A study from Bulgaria showed that pharmacists, as the most accessible health professionals, were able to detect mild to moderate depression in 55% of the tested patients. 34 Early detection of depression is one of the pharmacists' roles in depression care. 35 Screening for depression using suitable tools such as the Patient Health Questionnaire 2 (PHQ-2) and PHQ-7 is a task that should receive more attention within Egyptian pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The application of PC in pharmacies can not only improve the quality of life of patients, it may also prevent further complications, such as illnesses, as well as provide efficient and cost-effective treatment (17,18).…”
Section: Discussionmentioning
confidence: 99%